Biophysical Characteristic in Various Conditions of Heath Forest in East Belitung Residence, Province of Bangka Belitung Islands KARAKTERISTIK BIOFISIK PADA BERBAGAI KONDISI HUTAN KERANGAS DI KABUPATEN BELITUNG TIMUR, PROVINSI KEPULAUAN BANGKA BELITUNG - Iwan Hilwan (Jurnal Silvikultur Tropika, 2015)
Heath forest is one of forest ecosystem types in Indoensia as protected area and has specific condition and ecological functions. Quartz sands are main component of soil in heat forest floor which is very fragile for any disturbance. The damaged heath forest after quartz sand mined was very difficult to previous condition, therefore study of biophysical characteristics in primary and secondary heat forest are very important to conduct forest rehabilitation. The research result showed primer heath forest has higher plant diversity than secondary heath forest post mined 5 years and 15 years ago. Soil texture mostly sandy and soil chemistry is very acid (pH 3.6-5.3) with low fertility. Gelam (Melaleuca leucadendron) is a main pioneer plant species which can be used in revegetation program on post quartz mine land at Belitung Timur Residence.Key words: Acid soil, heath forest, Melaleuca leucadendron, quartz mining, revegetation